166k views
5 votes
Law of Exponents. Simplify each expression. Answers should be written with positive exponents.(-5p^6 times r^-9)^0

Law of Exponents. Simplify each expression. Answers should be written with positive-example-1
User GrepLines
by
4.6k points

1 Answer

4 votes

Solution:

Given the expression:


(-5p^6\cdot r^(-9))^0

Simplifying using the law of exponents,


\begin{gathered} (-5p^6\cdot r^(-9))^0=(-5* p^(-6)* r^(-9))^0 \\ \end{gathered}

but


a^(-b)=(1)/(a^b)

thus, we have


\begin{gathered} (-5* p^(-6)* r^(-9))^0=(-5*(1)/(p^6)*(1)/(r^9))^0 \\ =(-(5)/(p^6r^9))^0 \end{gathered}

From the zero index law of exponents,


a^0=1

This implies that


(-(5)/(p^6r^9))^0=1

Hence, the solution to the expression is 1

User Mikhail Genkin
by
5.5k points